TIPE-TIPE KALIMAT PASIF MURNI DALAM BAHASA JEPANG BERDASARKAN KATEGORI DAN PERAN SEMANTISNYA - Dedi Sutedi (Humaniora, 2013)
Japanese passive sentences have been separated only by function and category syntax, while the role of semantic received less attention. As a result, some issues still remain such as the existence of a passive sentence is one acceptable while others are not, even though the same syntactical function and category. This study tried to examine BJ passive sentences in terms of functionality, the category and also the role of passive sentences semantically pure (direct passive) are predicated BJ transitive verbs. The results of the data analysis is based on the function and structure of the purely passive category there are three kinds of structures (A, B, C), while based on semantic roles can be divided into eight types (I to VIII). Subject and complement the passive type. I must be filled by a noun animate each objective and agentive role; Type II - V, type VII, and VIII subjects filled by inanimate nouns and noun complement animate filled by the accepted determined by the semantic role and the type of verb; and passive type VI is both the subject and the complement to be filled by inanimate nouns.